Prevalence of viral hepatitis among the hospital staff in CSR between 1980 and 1982 - Seycková, J; Helcl, J; Walter, G (Journal of hygiene, epidemiology, microbiology, and immunology, 1984)
The hepatitis morbidity data were used to study prevalence rate of manifest viral hepatitis among the hospital staff members in CSR over a 3-year period between 1980 and 1982. This study showed that the overall hepatitis morbidity rate was 2.68 per 1,000 health personnel and was 3.6 times as high as that recorded in a normal population matched by age. The mean HBsAg positivity rate was 1.67 per 1,000 and was 5.8 times the rate in the control population group. The rate of HBsAg-negative cases of hepatitis was 1.01 per 1,000 health personnel and was higher than double the rate of morbidity encountered in an age-matched normal population. The highest morbidity rates were recorded in the lower-grade and auxiliary health personnel. When compared with an age-matched normal population the hospital staff members at all departments had distinctly higher morbidity rates than the general population, but the highest risk of acquiring viral hepatitis was evidently run by the personnel at departments of renal dialysis, biochemistry, hematology, infectious diseases, internal medicine, surgery, urology and TRD (tuberculosis and respiratory diseases). Of a total number of recorded cases of viral hepatitis those with HBsAg positivity predominated, especially at departments of urology, TRD, internal medicine, renal dialysis, psychiatry and hematology. Analyzed by specialty and professional status of personnel these viral hepatitis morbidity rates encountered among the hospital staff members seem to point to at least two conclusions: this infection in the health personnel is work-related and its transmission and spread is dependent on the frequency and intensity of contact with the blood and other secretions of infectious patients.
Keywords: Czechoslovakia; hepatitida B - antigeny povrchové; Risk; riziko; Československo; Hospital Departments; Hepatitis B Surface Antigens; Hepatitis, Viral, Human; Personnel, Hospital; Humans; virová hepatitida u lidí; nemocniční oddělení; epidemiologické metody; Epidemiologic Methods; lidé; personál nemocniční